Development of the trigger-controlling system for the proton computed tomography prototype - Ritjoho, Narongrit; Phumara, P.; Buanill, Y.; Boontueng, Phongnared; Songmoolnak, Arnon; Laojamnongwong, Natthawut; Charoonratana, L.; Sanghangthum, Taweap; Röhrich, Dieter; Schilling, Alexander; Aehle, Markus; Alme, Johannes; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2025)
Proton computed tomography (pCT) is an imaging reconstruction technique that uses protons’ positions, directions, and energy loss to generate a map of an object’s relative stopping power. In this work, the trigger-controlling system was designed and constructed to synchronize between components of our proposed pCT prototype and a proton beam at King Chulalongkorn Memorial Hospital (KCMH) in Bangkok. The controlling system can control the proton beam gating, a rotational stage, and ALPIDE sensors, which are parts of a tracker and a proton calorimeter of the pCT prototype. The controlling system was constructed based on the MEGA2560 microcontroller unit. The controlling system was verified by measuring the activated rows of the ALPIDE sensor at different proton extraction times. Additionally, the controlling system can control an array of six ALPIDE sensors, which could provide preliminary results of the proton calorimeter prototype.
Gesehen am 26.01.2026
Online veröffentlicht: 10. Dezember 2024